2017
DOI: 10.33736/ijbs.493.2017
|View full text |Cite
|
Sign up to set email alerts
|

Some New Estimates of Shadow Economy for 80 Countries Using Pooled Mean Group Estimator

Abstract: The purpose of this study is to estimates the size of the shadow economy for 80 countries from nine regions spanning the period 1975-2012 based on Tanzi-type currency demand approach (CDA). This study contributes to the literature in three distinct ways. First, we augment CDA regression with a macroeconomic uncertainty index (MUI). Second, the construction of the uncertainty index is based on the dynamic factor model (DFM). Third, the pooled mean group (PMG) estimator allows in capturing the heterogeneity acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The findings showed an asymmetric outcome across the countries, but with idiosyncratic characteristics such as the presence of large shadow economy in Thailand (average size of 66%–70% of GDP) as compared to Singapore (average size of 11%–15% of GDP) and Malaysia (average size of 16%–20% of GDP). The existence of the shadow economy tends to misrepresent the true size of a country’s economy (Tan, Habibullah, Kaliappan, & Radam, 2017).…”
Section: Data and Empirical Resultsmentioning
confidence: 99%
“…The findings showed an asymmetric outcome across the countries, but with idiosyncratic characteristics such as the presence of large shadow economy in Thailand (average size of 66%–70% of GDP) as compared to Singapore (average size of 11%–15% of GDP) and Malaysia (average size of 16%–20% of GDP). The existence of the shadow economy tends to misrepresent the true size of a country’s economy (Tan, Habibullah, Kaliappan, & Radam, 2017).…”
Section: Data and Empirical Resultsmentioning
confidence: 99%
“…Several studies have confirmed this positive connection empirically (e.g. Almenar et al, 2020;Hassan & Schneider, 2016b;Tan et al, 2017).…”
Section: Causes Of the Sementioning
confidence: 85%
“…Some studies attempted to estimate the size of Indonesia's shadow economy (see Table 1). For instance, Tan et al (2017) estimated that the average size of Indonesia's shadow economy during 1984 and 2012 was at around 28% of the official GDP. This figure is higher than the 19.8% average estimate by Medina and Schneider (2018).…”
Section: Estimating the Size Of Indonesia's Shadow Economymentioning
confidence: 99%
“…Based on the findings from the studies by the ADB (2011) and Rothenberg et al (2016), we induce a hypothesis that using financial sector development to provide greater access for the population to financial resources can reduce Indonesia's shadow economy. In this study, we investigate whether financial sector development can reduce Sources: Elgin and Oztunali (2012), Alm and Embaye (2013), Tan et al (2017), Medina and Schneider (2018), Wibowo and Sharma (2005), Panjaitan (2007), Nizar and Purnomo (2011), Samuda (2016) by calculating from the quarterly figures, Azwar and Mulyawan (2017) by averaging from the quarterly figures, and Ramadhan (2019). Elgin and Oztunali (2012) also provide the size of Indonesia'a shadow economy for the period 1960-1969 as 32.78, 33.08, 33.08, 33.13, 33.37, 33.59, 33.66, 33.71, 33.9 and 33.94, respectively. the size of Indonesia's shadow economy.…”
Section: Introductionmentioning
confidence: 99%